Frequency modulated systems in students with cochlear implant - Mora Espino, Rosa; Zenker Castro, Franz; Rodríguez Jiménez, María del Carmen; Mesa Suárez, José Luis; Coello Marrero, Ana (Auditio, 2021)
Due to the limitations of the Cochlear Implant (CI), the use of Frequency Modulated (FM) systems is advised to improve the signal-to-noise ratio in auditory-verbal learning environments in adverse acoustic conditions. Previous studies have shown that the acoustic conditions of most of the classrooms are acceptable for normal hearing students, however, these conditions are not appropriate for students with CI or other types of assistive listening devices. In this study, a simulation of the speech identification skills of a group of 1st year secondary school students is carried out based on the acoustic characteristics of the classroom. The Speech Audibility Index (AI) obtained for the analyzed classroom was 52%. From this AI, an estimate of speech perception is carried out for normal hearing students, with IC and IC + FM for the same position of the student in the classroom. Speech recognition is studied in three conditions of difficulty: (i) isolated high and low familiarity words (ii) phonemes in syllables and (iii) high and low familiarity words in simple and complex sentences. The results show that the linguistic competences of identification of the spoken message obtained by normal hearing students are higher than 92%. The estimate for students with CI showed significantly lower scores, being 34% in the recognition of novel words in complex sentences. The results obtained with IC + FM significantly improve linguistic performance, reaching 80% in the recognition of novel words in complex sentences. This study shows the acoustic barriers of the analyzed classroom for students with HF and the advantages of using FM systems.